The Fourth Plenary Session on Civil Matters vs. Jurisdictional Plenary Sessions: Disagreements, Contradictions, and Uncertainty. We need a new casatory plenary session on precarious possession - Pasco Arauco, Alan Augusto (2023)
The Fourth Casatory Plenary has encountered significant challenges due to the evolving circumstances. Throughout the past decade, a series of Jurisdictional Plenary Sessions have emerged, some of which have addressed issues that were not examined during the Fourth Plenary (such as the jurisdiction of Magistrate Judges to adjudicate precarious eviction cases or the potential waiver of conciliation in evictions arising from lease agreements with forfeiture clauses). Moreover, certain conclusions reached in these sessions openly contradict the precedents established in the Fourth Plenary (including the prescriptive period applicable to eviction claims or the possessory title in eviction lawsuits filed against family members).The current situation bears resemblance to the environment in which the Fourth Plenary was conducted, characterized by: (i) divergent perspectives on various aspects concerning precarious possession, (ii) a lack of certainty regarding the resolution of everyday challenges, (iii) inconsistent verdicts on identical matters and (iv) a pervasive atmosphere of uncertainty and unpredictability to the detriment of the litigants.An imperative exists for a new casatory plenary session focused on precarious possession that, akin to the Fourth Plenary in 2013, enables the restoration of order and furnishes a measure of predictability and certainty, at least in the medium term.